Sport, culture and society an introduction - Jarvie, Grant 1955-; Thornton, James; Mackie, Hector (Routledge, Taylor & Francis Group, an Informa Business, 2018)
Sport, Culture and Society : An introduction, 3rd Edition now in a fully revised, updated and expanded edition, this critical, challenging and comprehensive textbook introduces the study of sport, culture and society. International in scope, it challenges us to reactivate an audacious spirit of activism through sport. Full of contemporary examples, it places sport at the heart of the analysis and introduces the reader to every core topic and emerging area in the study of sport and society, including: the history and politics of sport; sport, gender and sexuality; sport, disability and advocacy; sport, race and racism; sport, violence and crime; sport and health; sport, globalisation and democracy; sport, media and cultural relations; sport and the environment; sporting cities and mega-events; sport, poverty and development. Each chapter includes a wealth of useful features, including Sport in Focus case studies, chapter summaries, guides to further reading, revision questions, practical projects, definitions of key concepts and weblinks. Additional teaching and learning resources -- including a testbank, resource list and glossary -- are available on a companion website. Sport, Culture and Society is the most broad-ranging, in-depth and thoughtful introduction to the sociocultural analysis of sport currently available and sets a new agenda for the discipline. It is essential reading for all students with an interest in sport.